The vindicating voice of Gamaliel Churata and José María Memet from the Andean philosophy - Viñamagua-Quezada, Glenda (2021)
Vindictive literature is a source of thought, resistance and commitment to human beings and society. These characteristics are present in the poetic compositions of Latin American writers who have oriented their work towards committed literature.  This study has brought together the voices of two representatives of Latin American poetry: Gamaliel Churata and José María Memet. They address the issue of vindication with respect to Western hegemony, so the reason for their poetic work is to show those who have been relegated from society. From this premise, the objective of this study is to expose the lines of thought developed in the literary production of these two poets. Churata's, configured from the indigenism, while Memet's from the contemporary Latin American poetry. In both historical moments it is demonstrated that the hegemonic thought does not dominate the language of the art, since this one, by itself, becomes a space where the vindication is constructed, as an alternative to the system imposed from the west. The analytical-synthetic method and documentary research have been used to carry out this study. Thus, the precepts of Andean philosophy will be applied from Josef Estermann's vision, in the interpretative analysis of the poems Holocaust of All Love for Him by Gamaliel Churata and The Mission of Man by José María Memet. In this way, the vindictive features that emerge in the mentioned lyric compositions regarding the principles of the Andean philosophy will be identified.